Endodontic treatment of the teeth with different root canal curvatures: Two case reports - Beljić-Ivanović Katarina; Teodorović Nevenka; Ostojić Dejan (Serbian Medical Society - Dental Section, Belgrade, 2009)
Endodontic treatment of the teeth with severe root canal curvatures has become one of the greatest problems in clinical practice. Recently, new instruments and techniques have been introduced in the endodontic procedure. The aim of this study was, on the basis of clinical practice, to show the possibilities of the endodontic treatment in the teeth with severely curved root canals, after dependable decision about endodontic instruments and techniques. This article presents a complete endodontic procedure in two teeth with different curvature shape of the root canal in patients that were treated at the Department of Restorative Dentistry and Endodontics, School of Dentistry, Belgrade. Coronal to apical 'crown down' technique was used for the root canal preparation with hand NiTi ProTaper instruments with progressive multicone design. The main reasons for choosing manual technique were complexity, shape of presented curvatures and better tactile sensation control of canal instruments in order to avoid possible mistakes and complications. Clinical X-rays of the teeth with permanent obturation clearly showed that extremes of the root canal morphology could be successfully solved by the right choice of all factors during endodontic procedure.